2012
DOI: 10.5056/jnm.2012.18.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rikkunshito (TJ-43) on Esophageal Motor Function and Gastroesophageal Reflux

Abstract: Background/Aims Rikkunshito (TJ-43), an herbal medicine, has been demonstrated to relieve gastroesophageal reflux symptoms. However, the effects of TJ-43 on esophageal motor functions have not been fully determined. This double-blind crossover study was performed to investigate the effects of TJ-43 on esophageal motor functions and gastroesophageal reflux. Methods The subjects were 10 normal male volunteers. Lower esophageal sphincter pressure and esophageal body perist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Stable ghrelin agonists have been reported to improve delayed gastric emptying in various experimental and clinical conditions associated with diabetes, postoperative and morphine-induced ileus and immune challenge [4,7,33,48,56,58]. Likewise, rikkunshito, a Japanese Kampo medicine acting as a ghrelin enhancer [50], alleviates gastroparesis [1,52], dyspepsia [1,25,52,54,61], post-operative gastric ileus [27,62], and gastroesophageal reflux disease [31,34,54] in experimental or clinical studies. A recent pilot clinical study also indicates that rikkunshito can ameliorate gastroparesis in PD patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…Stable ghrelin agonists have been reported to improve delayed gastric emptying in various experimental and clinical conditions associated with diabetes, postoperative and morphine-induced ileus and immune challenge [4,7,33,48,56,58]. Likewise, rikkunshito, a Japanese Kampo medicine acting as a ghrelin enhancer [50], alleviates gastroparesis [1,52], dyspepsia [1,25,52,54,61], post-operative gastric ileus [27,62], and gastroesophageal reflux disease [31,34,54] in experimental or clinical studies. A recent pilot clinical study also indicates that rikkunshito can ameliorate gastroparesis in PD patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Morita et al 22 reported that RKT at a standard dose did not have a significant effect on esophageal motor activity in healthy adults. This difference might be due to varying esophageal motor function between healthy adults and patients with PPI-refractory NERD.…”
Section: Discussionmentioning
confidence: 96%
“…49 It was reported to promote gastric adaptive relaxation in patients with functional dyspepsia. 50 Simotang Simotang (decoction of 4 powered drugs), one of the most commonly used Chinese herbal formulas, was administrated to chronically stressed mice daily for 7 days for the assessment of its effect on gastrointestinal motility.…”
Section: Alternative Medicine For Gastroparesismentioning
confidence: 99%